Mr. Bones - Reasoner, Charles (Mankato, MN Picture Window Books, a Capstone imprint, 2015)
In this book with simple rhyming text, Mr. Bones, a skeleton, cannot keep his bones together
English stories
1 2 13 15
Keywords: Halloween -- Juvenile fiction; Stories in rhyme